APPLICATION OF PERSONAL PROTECTIVE EQUIPMENT AS THE WORK SAFETY PROCEDURE IN THE WELDING PROCESS - Sunarji; Rachmasari Pramita Wardhani (MECHA JURNAL TEKNIK MESIN, 2021)
PPE is defined in the Regulations as: "all equipment (including clothing affording protection against the weather) which is intended to be worn or held by a person at work and which protects him against one or more risks to his health or safety". The Company should be make an appropriate and adequate assessment of the occupational health and safety risks from exposure to hazards in the workplace. For example, if there is a risk of objects falling from above, then the use of a safety helmet or helmet should be worn, etc. The Company should be make an appropriate and adequate assessment of the occupational health and safety risks from exposure to hazards in the workplace. For example, if there is a risk of objects falling from above, then the use of a safety helmet or helmet should be worn, etc. In this study discusses the use of PPE in the welding process, where it is known that almost every industrial company, both large and small, requires welding. and welding is one of the jobs that poses a risk to the safety and health of employees. Key words : PEE, welding, safety, procedure